IMPLIKASI PEMBIAYAAN KUR TERHADAP PENGEMBANGAN UMKM DI KECAMATAN MAKALE - Marniati; Ellyn Patadungan; Irgayanto Fahresi Patandean (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the effect of KUR financing on MSME development in Makale District. The assessment of KUR financing in this study is using 4 aspects, namely the accuracy of the use of funds, the amount of credit, the credit burden, and the procedure. The type of research used is a quantitative approach with a survey method. The population of this study were MSME actors who received KUR financing from Bank Sulselbar Makale Branch in Makale District totaling 159 people. Sampling was carried out using probability sampling technique using the slovin formula with an error rate of 1%, so that a sample of 61 respondents was obtained. The data collection technique was carried out through a questionnaire. The data analysis technique used simple linear regression analysis using the t test and using the SPSS version 23 application tool. The results of this study indicate that KUR financing has a positive and significant effect on the development of MSMEs. Keywords : KUR Financing; MSME Development; Bank Sulselbar Makale Branch